If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 11x + 15 Reorder the terms: 5 + 5x = 11x + 15 Reorder the terms: 5 + 5x = 15 + 11x Solving 5 + 5x = 15 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 5x + -11x = 15 + 11x + -11x Combine like terms: 5x + -11x = -6x 5 + -6x = 15 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + -6x = 15 + 0 5 + -6x = 15 Add '-5' to each side of the equation. 5 + -5 + -6x = 15 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 15 + -5 -6x = 15 + -5 Combine like terms: 15 + -5 = 10 -6x = 10 Divide each side by '-6'. x = -1.666666667 Simplifying x = -1.666666667
| 2m+45=-23 | | 6+5=0 | | 8(s+3)=7 | | -3(-4+4h)= | | 53x+14=43x+36 | | 30x=27x+11 | | 3w+116=500 | | 2(x+2)=x+10 | | x=10/0 | | 3(a-2)=4b+5 | | 3+-3(-2h+6)= | | 104=4(2-4x) | | x+41=70 | | 6[5-8(-4)]+12=x | | 6(-1+x)=-54 | | 891.25=7.5x+4.75y | | 0.80x+0.05(4-x)=0.10(-88) | | 11-3n=9n+2 | | 157=113-u | | 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 |